The effect of the use of Digital Learning Applications on Student Learning Outcomes in the era of Education 4.0 - Darwin, David; Astuti, Peni; Siregar, Hariani; Firayani, Firayani; Syamsudin, Ahmad (EduTech Journal, 2025)
This study aims to analyze the effect of the use of digital learning applications on student learning outcomes in the era of Education 4.0. The research method used is a qualitative approach with in-depth interviews with 10 student respondents, as well as observation of the use of applications in the classroom. The results showed that digital learning applications can improve students ' understanding of materials and motivation to learn, despite challenges related to technology access such as limited internet connectivity and devices. The use of digital applications also contributes to the development of students digital skills that are essential in the world of work. Teacher support and readiness of educational infrastructure are important factors in the successful implementation of the application. The research suggests the development of more interactive learning applications and more intensive training support for teachers and students.